Fasting hepatic de novo lipogenesis is not reliably assessed using circulating fatty acid markers - Rosqvist, F; McNeil, C; Pramfalk, C; Parry, S; Low, W; Cornfield, T; Fielding, B; Hodson, L (Oxford University Press, 2019)
Background Observational studies often infer hepatic de novo lipogenesis (DNL) by measuring circulating fatty acid (FA) markers; however, it remains to be elucidated whether these markers accurately reflect hepatic DNL. Objectives We investigated associations between fasting hepatic DNL and proposed FA markers of DNL in subjects consuming their habitual diet. Methods Fasting hepatic DNL was assessed using 2H2O (deuterated water) in 149 nondiabetic men and women and measuring the synthesis of very low-density lipoprotein triglyceride (VLDL-TG) palmitate. FA markers of blood lipid fractions were determined by gas chromatography. Results Neither the lipogenic index (16:0/18:2n–6) nor the SCD index (16:1n–7/16:0) in VLDL-TG was associated with isotopically assessed DNL (r = 0.13, P = 0.1 and r = −0.08, P = 0.35, respectively). The relative abundances (mol%) of 14:0, 16:0, and 18:0 in VLDL-TG were weakly (r ≤ 0.35) associated with DNL, whereas the abundances of 16:1n–7, 18:1n–7, and 18:1n–9 were not associated. When the cohort was split by median DNL, only the abundances of 14:0 and 18:0 in VLDL-TG could discriminate between subjects having high (11.5%) and low (3.8%) fasting hepatic DNL. Based on a subgroup, FA markers in total plasma TG, plasma cholesteryl esters, plasma phospholipids, and red blood cell phospholipids were generally not associated with DNL. Conclusions The usefulness of circulating FAs as markers of hepatic DNL in healthy individuals consuming their habitual diet is limited due to their inability to discriminate clearly between individuals with low and high fasting hepatic DNL.